English suffixes and their productiveness in word formation / Nguyễn Thị Hoa; NHDKH Dr Nguyen Thi Thu Huong - Nguyễn, Thị Hoa
The major aim of the study is to clarify English suffixes and their productiveness in word formation. The objectives of the study is to systematize , clarify, carry out a thorough scrutiny into productive suffixes and discover the Vietnamese learners’ mistakes, find out solutions, help students get a deeper understanding of English suffixes in general and English suffixes in particular. The study was completed by several means of main methods: descriptive and analysis method. This thesis has contributed some research results: the role of suffixes in English word formation, the types of English suffixes, productive suffixes and the problems are caused by suffixes in English for Vietnamese learners.